Design de Livros e Signos Visuais – O Design e a Contextualização Imagética no Livro Didático Escolar - Cerqueira, Ana Tereza Carvalho (2009)
The present study it brings the quarrel of the pertaining to school didactic book, First Texts, raising it while example of a graphical project with ample social insertion. E when observing as the percipient elements (format, edges, typography, colors, space distribution, among others) intervenes with the visual potentiality of the book, relates possible trends and perspectives adopted in the imagética contextualização of verbal and not verbal elements, so that the study object reaches its function in the aid to the apprehension of the verbal language of children in the first pertaining to school year.